Recognition of Children Outside of Marriage Reviewed from Positive Law in Indonesia - Muhammad Erdiansyah Ceisar Ramadhan; Wahyu Prawesthi; Sri Sukmana Damayanti (Civiliza Publishing, 2026)
The recognition of children born out of wedlock remains a significant legal issue within the framework of Indonesian positive law. Children, as subjects of law, are entitled to protection and equal treatment regardless of the circumstances of their birth. However, prior to the Constitutional Court Decision Number 46/PUU-VIII/2010, children born outside lawful marriage were legally recognized as having civil relations only with their mother and her family, resulting in limited access to paternal rights. This normative juridical research employs a statute and conceptual approach to examine the legal regulation and protection of children born out of wedlock under Indonesian law. The study analyzes the Civil Code, the Marriage Law, the Population Administration Law, and relevant Constitutional Court rulings. The findings indicate that, following the Constitutional Court’s decision, children born out of wedlock may establish civil legal relations with their biological father, provided that biological paternity is proven through lawful evidence, including scientific methods such as DNA testing. Nevertheless, practical challenges remain, particularly concerning procedural requirements and judicial discretion, which may hinder full legal protection. Therefore, stronger regulatory harmonization and legal certainty are necessary to ensure comprehensive protection of children’s civil rights.